Pengaruh Profitabilitas, Investment Opportunity Setdan Free Cash Flow Pada Kebijakan Dividen - Utama, Ngurah Surya Pranajaya; Gayatri, Gayatri (E-Jurnal Akuntansi; Vol 22 No 2 (2018), 2018)
The dividend policy is a decision on corporate profit sharing. The dividend policy issued by company through the General Meeting of Shareholders (AGM) becomes an important factor to be considered for potential investors. Therefore, the company must pay attention to the factors in determining the decision regarding the dividend policy. Dividend policy decisions need to be considered by the company to get an optimal results. This study aims to obtain empirical evidence on the effect of profitability, investment opportunity set, and free cash flow on dividend policy.This research was conducted at a manufacturing company listed on Indonesia Stock Exchange 2012-2016. The sampling method was purposive sampling. Data analysis technique was multiple linear regression. Based on the research, it’s known that profitability is proxied by return on assets (ROA) has a positive effect on dividend policy. Meanwhile, investment opportunity set and free cash flow have no effect on dividend policy. Keywords: Dividend policy, profitability, investment opportunity set, and free cash flow